Valeological Preparation of Students as Means of Creation of Positive Image of Future Teacher - O. A. Efits; S. S. Akhtamova (Научный диалог)
The question of valeological preparation of students - future teachers is considered. The relevance of the study is determined by the promotion of health problems among the priorities of social development of our society. The authors believe that the efforts of medical specialists are not enough to support and protect the health of citizens of the country. The formation of the priority of health and motivation for a healthy lifestyle among the younger generation is associated with the need to combine the efforts of the family, cultural workers and the pedagogical community. A key role in teaching the responsibility of the younger generation for their personal health is given to a modern school. The idea that only professionally trained teachers are able to solve a socially significant problem is consistently carried out. Particular attention is paid to the methods of determining the level of individual physical health of students, mastering of which learns future teachers to build an active model of healthy lifestyle. The article presents the experience of implementation of educational programs for training students of the Lesosibirsk Pedagogical Institute - branch of Siberian Federal University. The methods of teaching are characterized. It is assumed that students, mastering the methods of maintaining health, acquire readiness for future teaching activities: they will be able to create a positive image of a teacher to promote a healthy lifestyle and to demonstrate the idea of direct dependence of life success on good health.